Stereological analysis of gonads from diploid and triploid fish yellowtail tetra Astyanax altiparanae (Garutti & Britski) in laboratory conditions - Nascimento, Nivaldo Ferreira do [UNESP]; Siqueira-Silva, Diogenes Henrique de; Pereira-Santos, Matheus [UNESP]; Fujimoto, Takafumi; Senhorini, Jose Augusto; Okada Nakaghi, Laura Satiko [UNESP]; Yasui, George Shigueki (Cambridge Univ Press, 2017)
This study aimed to examine the gonadal morphology of diploid and triploid fish through stereological analysis. Triploid individuals were obtained after temperature shock (40 degrees C for 2 min) at 2 min post-fertilization and reared until 175 days post-fertilization (dpf). Intact eggs were used to obtain the diploids. Gonads were collected for histological analysis at 83, 114, 144 and 175 dpf. Diploid females and males presented normal oogenesis and spermatogenesis through all the experimental period. Conversely, stereological analysis revealed that triploid females were sterile and oogonia were the prevalent cell type in the ovaries. Triploid males presented increased amounts of spermatocyte cysts and a large area of lumen when compared with diploids and in addition the amount of spermatozoa was lower than that observed for diploids. However, some triploid males presented spermatogenesis similar to diploids. Therefore, we concluded that triploidization is an interesting alternative to produce sterile individuals in A. altiparanae.
Keywords: Chromosome set manipulation; Fish reproduction; Germ cells; Growth; Sterility